2018
DOI: 10.1096/fj.201701095r
|View full text |Cite
|
Sign up to set email alerts
|

Cystathionine β‐synthase regulates mitochondrial morphogenesis in ovarian cancer

Abstract: Deregulation of mitochondrial morphogenesis, a dynamic equilibrium between mitochondrial fusion and fission processes, is now evolving as a key metabolic event that fuels tumor growth and therapy resistance. However, fundamental knowledge underpinning how cancer cells reprogram mitochondrial morphogenesis remains incomplete. Here, we report that cystathionine β-synthase (CBS) reprograms mitochondrial morphogenesis in ovarian cancer (OvCa) cells by selectively regulating the stability of mitofusin 2 (MFN2). Cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(48 citation statements)
references
References 51 publications
1
47
0
Order By: Relevance
“…Similarly, treatment with the MEK inhibitor, PD325901, results in dramatic decline in both ERK and Drp1616 phosphorylation, effectively reversing mitochondrial fragmented phenotype in oncogenic Ras-induced embryonic kidney cells (Kashatus et al, 2015). JNK activation is connected to Mfn2 but not Mfn1 turnover (Chakraborty et al, 2018). Leboucher et al demonstrated FIGURE 1 | Phosphorylated Drp1-mediated mitochondrial fission.…”
Section: Mitogen-activated Protein Kinases (Mapks)mentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, treatment with the MEK inhibitor, PD325901, results in dramatic decline in both ERK and Drp1616 phosphorylation, effectively reversing mitochondrial fragmented phenotype in oncogenic Ras-induced embryonic kidney cells (Kashatus et al, 2015). JNK activation is connected to Mfn2 but not Mfn1 turnover (Chakraborty et al, 2018). Leboucher et al demonstrated FIGURE 1 | Phosphorylated Drp1-mediated mitochondrial fission.…”
Section: Mitogen-activated Protein Kinases (Mapks)mentioning
confidence: 99%
“…JNK activation is connected to Mfn2 but not Mfn1 turnover ( Chakraborty et al, 2018 ). Leboucher et al demonstrated that JNK mediated the phosphorylation of Mfn2 at Ser27 of sarcoma U2OS cells in response to cellular stress, which contributed to ubiquitin-proteasome degradation in Mfn2 and enhanced apoptosis ( Leboucher et al, 2012 ).…”
Section: Regulatory Mechanisms Of Mitochondrial Dynamicsmentioning
confidence: 99%
“…It is worth noting that the higher expression of Mfn2 has also been reported in lung adenocarcinoma tissues as compared to adjacent normal tissues, and Mfn2 knockdown results in impaired cancer cell proliferation (81). In ovarian cancer (82), breast cancer (83), and melanoma (84), Mfn2 knockdown suppresses oxygen consumption rate (OCR). In pancreatic cancer cells (PANC-1), Mfn2 knockdown enhances mitochondria-dependent energy metabolism by promoting activity of electron transport chain complexes (85).…”
Section: Mitochondrial Fusion and Fission Shape Cancer Metabolismmentioning
confidence: 99%
“…Additionally, we previously reported cysteine concentration (total and protein bound) in peripheral blood as a promising marker for screening, early diagnosis, outcome, and follow-up of ovarian cancer [25]. The overexpression of CBS associated with H 2 S generation was reported in several ovarian cancer cell lines and tumor models and was proposed to contribute to mitochondrial morphogenesis reprogramming [26], energy metabolism regulation [27], and deregulation of lipid metabolism [26], thereby promoting tumor growth and chemoresistance [12]. Indeed, CBS inhibition may afford anti-tumor activity and abrogation of chemoresistance via attenuated GSH synthesis and nuclear metallothionein expression [12,28].…”
Section: Introductionmentioning
confidence: 99%